(untitled) (Linguist, 2025)
This study examines the status of linguistic minorities in Europe within the evolving legal and political framework of the European Union. Although the principle of equality among the official languages of Member States has been recognized since the establishment of the European Economic Community in 1957, such recognition has largely excluded the extensive linguistic diversity represented by minority languages. The paper highlights the scale and heterogeneity of linguistic minorities across Europe and discusses the conceptual and legal challenges involved in defining minorities and minority languages. It further analyzes the main European normative instruments developed for their protection, particularly the European Charter for Regional or Minority Languages and the Framework Convention for the Protection of National Minorities, emphasizing their scope, implementation mechanisms, and limitations. In addition, the study traces the gradual incorporation of linguistic diversity into EU policies, especially following the adoption of the Charter of Fundamental Rights and the Lisbon Treaty. The paper concludes that, despite significant normative progress, the effective protection of minority languages remains uneven and largely dependent on the political will of individual Member States.